2017
DOI: 10.1016/j.nmd.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Limb girdle muscular dystrophy type 2I: No correlation between clinical severity, histopathology and glycosylated α-dystroglycan levels in patients homozygous for common FKRP mutation

Abstract: Limb girdle muscular dystrophy type 2I (LGMD2I) is a progressive disorder caused by mutations in the FuKutin-Related Protein gene (FKRP). LGMD2I displays clinical heterogeneity with onset of severe symptoms in early childhood to mild calf and thigh hypertrophy in the second or third decade. Patients homozygous for the common FKRP mutation c.826C>A (p.Leu276Ile) show phenotypes within the milder end of the clinical spectrum. However, this group also manifests substantial clinical variability. FKRP deficiency ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
(58 reference statements)
6
26
0
Order By: Relevance
“…Some previous studies found higher proportion of females with sarcoglycanopathies, while other studies did not; and male predominance in LGMD2I/LGMD‐R9‐FKRP‐related was not previously reported. Further larger cohorts on these subtypes should clarify if there are sex differences in these autosomal recessive diseases or whether these findings reflect selection bias. The finding of male predominance in LGMD2L/LGMD‐R12‐anoctamin5‐related is well established, although little is understood …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies found higher proportion of females with sarcoglycanopathies, while other studies did not; and male predominance in LGMD2I/LGMD‐R9‐FKRP‐related was not previously reported. Further larger cohorts on these subtypes should clarify if there are sex differences in these autosomal recessive diseases or whether these findings reflect selection bias. The finding of male predominance in LGMD2L/LGMD‐R12‐anoctamin5‐related is well established, although little is understood …”
Section: Discussionmentioning
confidence: 99%
“…LGMD-R9-FKRP-related was not previously reported. 35,36 Further larger cohorts on these subtypes should clarify if there are sex differences in these autosomal recessive diseases or whether these findings reflect selection bias. The finding of male predominance in LGMD2L/…”
Section: Sex Effectmentioning
confidence: 99%
“…In both LGMD2I and WWS/MEB, FKRP protein is expressed at relatively normal levels; however, the amount of glycosylation of α-dystroglycan is somewhat reflective of the disease severity and classification (45). There are conflicting reports as to whether or not the levels and complexity of α-dystroglycan glycosylation are faithfully representative of disease severity and classification of FKRP pathogenic variants (16). Recent work in gene therapy has shown that overexpression of full-length FKRP protein using systemic AAV delivery can block muscle wasting and cardiac symptoms associated with LGMD2I (33,46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having severely reduced levels of glycosylated α-dystroglycan protein, these patients have decreased levels of laminin matrix proteins that may explain some of the severe retinal and brain pathologies (15). While the genetic causes of both LGMD2I and WWS/MEB have been identified, the consequential disparate clinical pathologies between the 2 disorders with the same causative gene remain poorly understood (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is no correlation between the clinical disease severity, histopathology, and glycosylated α -DG levels in patients with LGMD2I [ 10 ]. Muscle magnetic resonance imaging (MRI) is a noninvasive tool that can contribute to the diagnosis and assessment of disease severity and progression in a number of neuromuscular disorders.…”
Section: Introductionmentioning
confidence: 99%